Pendidikan Kewirausahaan dan Lingkungan Sosial Terhadap Intensi Berwirausaha Dengan Efikasi Diri Sebagai Variabel Mediasi - Saidah Mahbubah; Riza Yonisa Kurniawan (JURNAL SOSIAL EKONOMI DAN HUMANIORA, 2022)
Unemployment is an economic problem that needs attention in Indonesia. The cause of unemployment is because the number of jobs is not equal to the number of the workforce. Entrepreneurship can increase employment and help reduce unemployment. This study aims to analyze self-efficacy as a mediating variable of entrepreneurship education and social environment on entrepreneurial intentions. This research includes associative research using quantitative research methods. Data collection was carried out using a questionnaire instrument. The population in this study was 118 students with 91 students as the sample. The data were analyzed using the Successice Interval (MSI) method and the Stuctural Equation Modeling (SEM) technique using the WarpPLS device. The results of the study stated that a significant and positive effect of entrepreneurship education was found on self-efficacy, found a significant and negative effect of entrepreneurship education on entrepreneurial intentions, found a significant and positive influence on the social environment on self-efficacy and entrepreneurial intentions, found a significant and positive influence on entrepreneurial efficacy. Self-efficacy on entrepreneurial intentions, found an insignificant and positive effect of self-efficacy as a mediating influence of entrepreneurship education on entrepreneurial intentions, and found a significant and positive effect of self-efficacy as a mediating influence of social environment on entrepreneurial intentions.